Mediating effect of deviant peers on the relationship between sensation seeking and lifetime smoking among high school students. (4th May 2018) - Park, Sunhee; Kim, Junghee; Hwang, Heejin
ABSTRACT: Background : Despite the greater risk of lifetime smoking among high sensation seekers, it is difficult to change a sensation seeking tendency through interventions. Therefore, it is important to identify a modifiable factor mediating the link between these two conditions in order to weaken or disconnect the association. Objectives : Based on the literature, deviant peers may play a pivotal role in explaining this association. Thus, we aimed to investigate the mediating effect of deviant peers on the association between sensation seeking and lifetime smoking among Korean adolescents. Methods : We analyzed secondary data obtained from 876 high school students. Approximately 51% of the participants were male. In order to investigate the mediating effect of deviant peers after controlling for 16 factors, we tested an indirect effect in a simple mediation model using the PROCESS macro, which is a regression-based approach. Results : We found a significant total effect of sensation seeking on lifetime smoking: greater risk of lifetime smoking among high sensation seekers. In addition, we found a significant mediating effect of deviant peers on the association between the two conditions. Specifically, higher sensation seeking successfully predicted a greater number of deviant peers, which, in turn, successfully predicted greater risk of lifetime smoking. Conclusion : Given difficulties in directly changing levels of sensation seeking and the significant mediating effect of deviant peers on the association between the two conditions, prevention strategies focusing on peers may be advantageous for high sensation seekers in reducing their risk of lifetime smoking in adolescence.